THE EFFECT OF TRANSFER PRICING, SALES GROWTH, AND INVENTORY INTENSITY ON TAX AVOIDANCE IN FOOD AND BEVERAGE COMPANIES - Putri Alika Ramadhina (Research Trend in Technology and Management, 2023)
This study approaches quantitative methods to determine the effect of transfer pricing, sales growth, and inventory intensity on tax avoidance. The research uses secondary data from the company's annual report. The annual report can be accessed on the company's official website, www.idx.co.id and www.idnfinancials.com. The study population consisted of 38 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during 2018 and 2021. The sampling used Purposive sampling method with a total sample of 72 company data obtained during 2018-2021. In this test, there are outlier data so that 11 samples are removed so that the data is normally distributed and the number of samples becomes 61 samples. This study uses multiple linear regression analysis techniques. The results of the research obtained are transfer pricing and sales growth have a negative and significant effect on tax avoidance. While inventory intensity has a positive and significant effect on tax avoidance.